2014
DOI: 10.1007/s00265-014-1790-z
|View full text |Cite
|
Sign up to set email alerts
|

Uniform predation risk in nature: common, inconspicuous, and a source of error to predation risk experiments

Abstract: Previous studies indicate that when predation risk is uniform across habitats, foragers concentrate their exploitation in fewer patches. Although uniform predation risk may seem rare in nature, some scenarios might cause it. Testing all scenarios in a single experiment is unfeasible; therefore, we developed a model that points whether concentration of exploitation in specific habitats due to uniform risk requires parameter values similar to what is found in literature. This model was based on Brown's (Behav Ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Leaf abscission presented no effects on predation of sloths. Although we predicted increased probability of arboreal prey detection under leafless conditions in the semi-deciduous forests of central Panama, forest areas dominated by leafless trees and/or woody lianas may be consistently avoided by prey species relying on concealed foraging activity (Menezes, Kotler & Mourão, 2014;Menezes, Mourão & Kotler, 2017). For a sloth, leafless tree crowns offer little if any protective cover and no food resources.…”
Section: Modelmentioning
confidence: 65%
See 1 more Smart Citation
“…Leaf abscission presented no effects on predation of sloths. Although we predicted increased probability of arboreal prey detection under leafless conditions in the semi-deciduous forests of central Panama, forest areas dominated by leafless trees and/or woody lianas may be consistently avoided by prey species relying on concealed foraging activity (Menezes, Kotler & Mourão, 2014;Menezes, Mourão & Kotler, 2017). For a sloth, leafless tree crowns offer little if any protective cover and no food resources.…”
Section: Modelmentioning
confidence: 65%
“…Conversely, the dry season often induces leaf abscission in trees and woody lianas (Souza, Gandolfi & Rodrigues, 2014), which may limit food availability and shelter to arboreal folivores. The combination of reduced cover and limited food resource availability can enhance predation risk (Menezes, Kotler & Mourão, 2014;Menezes, Mourão & Kotler, 2017). The seasonal variation may modify the range of thermal microhabitats available to a prey species.…”
Section: Introductionmentioning
confidence: 99%
“…Kotler and Brown 1999 ; Dall et al 2000 ). Risk-uniform landscapes have received very little attention, albeit—from a forager’s perspective—they are not uncommon (but see Eccard and Liesenjohann 2008 ; Eccard et al 2008 ; Liesenjohann and Eccard 2008 ; Menezes et al 2014 ). The available studies revealed that under uniform risk foragers may exploit a few patches only, particularly under high risk (Eccard and Liesenjohann 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of reduced cover and limited food resource availability can enhance predation risk (Menezes, Kotler & Mourão, 2014;Menezes, Mourão & Kotler, 2017). The seasonal variation may modify the range of thermal microhabitats available to a prey species.…”
Section: Introductionmentioning
confidence: 99%